Niche segregation facilitates coexistence between native and introduced fishes in a deep Patagonian lake - Juncos, Romina (2015)
Species introductions force sympatry between species that did not coevolve. Introduced salmonids have coexisted with native fish since the early 20th century in Patagonian water bodies, thus generating questions about the mechanisms that facilitate their coexistence. We analyzed the trophic and spatial intra- and inter-specific relationships established among native and salmonid species in a deep oligotrophic lake of Patagonia in order to determine niche partitioning patterns as strategies for their coexistence. Salmonids were more generalist feeders, while native species had narrower trophic niches. Native fish and introduced salmonids partitioned food, mainly through the consumption of the crayfish Samastacus sp. and the native galaxiid Galaxias maculatus, respectively. The diet of most species changed with body size, shifting from insects/amphipods to the larger G. maculatus and crayfish. Trophic interactions varied with season, in association with prey seasonality. In general, fishes feeding on the same prey were captured in the same depth strata, indicating common use of food and space. Our results provide new evidence on the trophic ecology of a mixed fish community (exotic-native), supporting the idea that native and non-native fishes could be avoiding negative interactions (e.g., competition) through trophic and spatial resource partitioning.